2022
DOI: 10.1038/s41598-022-09504-2
|View full text |Cite
|
Sign up to set email alerts
|

Label free identification of the different status of anemia disease using optimized double-slot cascaded microring resonator

Abstract: An optical-based label-free biosensors including two indirectly coupled double-slot-waveguide-based microring resonator was designed and optimized for sensing purpose. Then, the optimized system was applied for the detection of hemoglobin concentration in anemia disease. The results were simulated based on the variational finite-difference time domain (varFDTD) method using the Lumerical software (Mode solutions) and the optimum geometrical parameters were determined to realize an optimum light transmission vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Further, the difference of TE 0 and TM 0 propagation constants, i.e., ∆β(λ, n c ) as a function of the wavelength at considered film thicknesses is plotted as shown in Fig. 5, and hence phase difference dependence ∆φ(λ, n c ) is calculated using Equation (10). It is clear from this figure that at film thickness of 300 nm, 350 nm, and 400 nm, ∆β(λ, n c ) first increases up to their respective maximum value 0.01683 µm −1 , 0.01446 µm −1 , and 0.01265 µm −1 , and then starts decreasing under considered wavelength range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the difference of TE 0 and TM 0 propagation constants, i.e., ∆β(λ, n c ) as a function of the wavelength at considered film thicknesses is plotted as shown in Fig. 5, and hence phase difference dependence ∆φ(λ, n c ) is calculated using Equation (10). It is clear from this figure that at film thickness of 300 nm, 350 nm, and 400 nm, ∆β(λ, n c ) first increases up to their respective maximum value 0.01683 µm −1 , 0.01446 µm −1 , and 0.01265 µm −1 , and then starts decreasing under considered wavelength range.…”
Section: Resultsmentioning
confidence: 99%
“…An optical biosensor consists of a bio-receptor to capture the target analyte and a transducer whose optical properties, such as absorption, reflectance, emission, and interferometeric pattern, is altered in the presence of analyte [7,8]. There are various popular methods for monitoring the change in optical properties, and some of these methods are surface plasmon resonance (SPR) [9], microring resonators [10,11], reflectometric interference spectroscopy (RifS) [12], photonic interferometric biosensors [13], and planar waveguide interferometers [9,14]. Out of these methods, it is suggested that the interferometeric analysis provides larger sensitivity by operating them on single wavelength [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various approaches to implementing refractometry systems, phase-sensitive circuits are the most attractive in terms of technological viability and efficiency. Widely used schemes for detecting changes in the physical properties of an analyte include fiber (FBG) and waveguide (WBG) Bragg gratings [ 4 , 5 , 6 , 7 ], waveguide Mach–Zehnder interferometers (MZI) [ 8 , 9 , 10 ], and microring (MRR) or microdisk (MDR) resonators [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among all existing types of sensors on PICs, MRR is the most used [ 17 ]. MRRs have great potential to implement label-free detectors because they are fast, energy-efficient, and have a significant sensitivity to detect biomolecules in liquids and gases [ 12 , 13 ]. MRR fabrication technology is widely applied, and silicon MRRs can be integrated into a microfluidic system [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation